Deteksi IgG dan IgM anti antigen 85b pada serum penderita tuberkulosis = Detection of IgG and IgM Anti 85B Antigen in Sera from Tuberculosis Patients - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT To develop a diagnostic tool for tuberculosis, this study was performed by detecting spesific IgG and IgM against M. tuberculosis antigen in tuberculosis patients. Sera were collected from 30 tuberculosis patients, 30 patients with other lung disease but negative acid fast bacilli, 60 leprosy patients (30 TT and 30 LL), and 30 healthy controls. Diagnosis of tuberculosis was based on clinical features, positif acid fast bacilli, minimal lesion in radiologic examination without any sign of complications. The sera were tested by IgG and IgM ELISA using M. tuberculosis antigen 85B and 65 kD as control. Sensitivity and spesificity of IgG anti 85B antigen test were 60 % and 83,3% respectively, and could differentiate between tuberculosis from healthy control and leprosy, but coud not differentiate tuberculosis from other lung disease. The result of IgM anti 85B antigen assay showed an extremely low sensitivity (0 %), and there was no significant difference between each group. Although the result showed that spesific IgG against tuberculosis 85B antigen can be detected in tuberculosis patients, however as the low sensitivity and spesificity of the test, this antigen can not be recommended for diagnostic test for tuberculosis.